Upper Limb Dysfunction Increases Fear of Falling in People With Stroke - Bilek, Furkan (Ibn Sina Trust, 2021)
Objective: Our study was planned to investigate the effect of upper limb function on fear of falling in stroke patients. Materials and methods: A total of 61 patients, 33 women with chronic hemiplegia or hemiparesis, were included in the study. Patients' upper limb motor condition was obtained using the Fugl-Meyer Upper Extremity Rating Scale (FMA), upper limb function Arm Motor Ability Test (AMAT) and fear of falling International Fall Efficacy Scale (FES-I). Standard Mini-Mental Examination scale was used to exclude patients with mental disorders. Results and Discussion: There was a highly significant negative correlation between FES-I and AMAT and FMA scores (p <0.001, r = -0.926 and r = -0.888, respectively). There was also a significant positive correlation between FMA and stroke time (p <0.05). It was observed that the fear of falling with the level of upper limb dysfunction increased in parallel. Conclusion: It suggests situation that this is due to the fact that they experience balance problems as a result of upper limb dysfunction and when they fail to reveal protective reflexes in a quality way
Keywords: Fear of falling; stroke; upper limb; hemiplegia; upper limb function